1994
DOI: 10.1093/jnci/86.9.673
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Comparing Perioperative Chemotherapy and Surgery With Surgery Alone in Resectable Stage IIIA Non-Small-Cell Lung Cancer

Abstract: This clinical trial strengthens the validity of using perioperative chemotherapy in the management of patients with resectable stage IIIA non-small-cell lung cancer. Further investigation of the perioperative chemotherapy strategy in earlier stage lung cancer is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
375
3
18

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,036 publications
(404 citation statements)
references
References 0 publications
8
375
3
18
Order By: Relevance
“…On the other hand, several phase III studies have shown that cisplatincontaining induction chemotherapy may increase survival rate in stage IIIA or IIIB locally advanced non-small cell lung cancer (LAD-NSCLC) patients. Two randomized studies demonstrated increased survival in stage IIIA NSCLC patients if two to three cycles of chemotherapy were given before surgery (Rosell et al, 1994;Roth et al, 1994). In inoperable patients, induction with cisplatin plus vinblastine followed by radiotherapy demonstrated long-term survival advantage over radiotherapy alone in a randomized study (Dillman et al, 1996) and was confirmed subsequently by an intergroup study (Sause et al, 1995).…”
mentioning
confidence: 94%
“…On the other hand, several phase III studies have shown that cisplatincontaining induction chemotherapy may increase survival rate in stage IIIA or IIIB locally advanced non-small cell lung cancer (LAD-NSCLC) patients. Two randomized studies demonstrated increased survival in stage IIIA NSCLC patients if two to three cycles of chemotherapy were given before surgery (Rosell et al, 1994;Roth et al, 1994). In inoperable patients, induction with cisplatin plus vinblastine followed by radiotherapy demonstrated long-term survival advantage over radiotherapy alone in a randomized study (Dillman et al, 1996) and was confirmed subsequently by an intergroup study (Sause et al, 1995).…”
mentioning
confidence: 94%
“…[4][5][6][7][8] Two of these studies involved small cohorts (n ¼ 60) that included mainly stage IIIA, N2 disease, and showed a significant survival advantage associated with induction chemotherapy compared with surgery alone. 5,6 None of the other trials reported any beneficial outcome for bimodality therapy compared with surgery alone.…”
mentioning
confidence: 99%
“…[4][5][6][7][8] Two of these studies involved small cohorts (n ¼ 60) that included mainly stage IIIA, N2 disease, and showed a significant survival advantage associated with induction chemotherapy compared with surgery alone. 5,6 None of the other trials reported any beneficial outcome for bimodality therapy compared with surgery alone. 4,7,8 Induction treatment using combined concurrent chemoradiotherapy prior to surgery resulted in NSCLC cure rates of 30% to 40% at 5 years and appeared to improve survival over treatment with surgery alone.…”
mentioning
confidence: 99%
“…Several small randomised studies (Pass et al, 1992;Rosell et al, 1994;Roth et al, 1994) have demonstrated a benefit from neoadjuvant treatment in locally advanced disease (stage IIIA). In a large trial involving 355 patients with stage IB -IIIA NSCLC, a trend towards survival benefit was seen from neoadjuvant chemotherapy (median survival 37 months vs 26 months for surgery alone; P ¼ 0.15) (Depierre et al, 2002).…”
mentioning
confidence: 99%